Penerapan Prinsip Good Corporate Governance dalam Hukum Perusahaan: Mengoptimalkan Akuntabilitas dan Transparansi di Perusahaan Indonesia : Optimizing Accountability and Transparency in Indonesian Companies - Ana Ragita Pakpahan, Dosni; Grecya Sihombing, Nency; Sangadah, Nur (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This article discusses the implementation of Good Corporate Governance (GCG) principles in corporate law as an effort to optimize accountability and transparency within companies. GCG serves as a framework that ensures corporate management acts ethically and responsibly, while also complying with applicable laws and regulations. By applying GCG principles, companies can enhance stakeholder and investor trust, which in turn contributes to improved performance and corporate value. This research employs a normative legal approach and qualitative analysis of relevant secondary data sources. The analysis reveals that implementing GCG is not only essential to meet regulatory demands but also to build a transparent and accountable corporate culture, thereby reducing the risk of power abuse and enhancing the company’s reputation in the public eye.